Managing women's post retirement career in law enforcement organisations: Lessons from developed nations for emerging economies - Anthony, Mary *; Soontiens, Werner (Inderscience, 2018)
This paper explores protean careers US and Australian policewomen seek post retirement. Two research questions address why policewomen seek a protean career after retirement from law enforcement. The study utilised a phenomenological approach involving semi-structured interviews conducted with 40 policewomen in middle and top management roles in the USA and Australia. Analysis of data involved coding for emergent themes based on the interpretivist research philosophy. Interview transcripts of 40 policewomen from these countries show that more than 90% of the women from the USA were aggressively seeking to develop protean careers while that was not the case in Australian law enforcement. The paper demonstrates the current situation in the USA and Australia; and how it can conceptualise models for emerging economies. It provides important lessons for women in organisations, especially in emerging economies on how to create protean careers post retirement.